Karakteristik Kimia dan Sensori Crackers dengan Penambahan Tepung Campolay (Pouteria campechiana) dan Teping Ikan Teri Nasi (Stolephorus sp) - Indri Setiawati; Noli Novidahlia; Raden Siti Nurlaela (JURNAL AGROINDUSTRI HALAL, 2024)
ingredients can be added to the manufacture such as campolay flour and ground wheat flour to increase the nutritional content of the crackers. This study aims to make crackers with the addition of campolay flour and rice anchovy flour as a form of food diversification and to find the selected formulation from the ratio of wheat flour: campolay flour: rice anchovy flour. This study used a completely randomized design (CRD) with one treatment factor, namely the ratio of wheat flour : campolay flour : anchovy flour (80:15:5), (70:20:10), (60:25:15), ( 50:30:20). Product analysis includes chemical analysis of water content, acid insoluble ash content, and protein content as well as sensory and hedonic quality tests as a determinant of selected products. The selected treatment was then subjected to further chemical analysis including calcium levels and beta-carotene levels. Data analysis and research used (ANOVA) with Duncan's further test with a 95% confidence interval. The results showed that the selected crackers were treated with a ratio of wheat flour: campolay flour: anchovy flour (70:20:10) with a quality that did not smell of campolay flour, smelled of anchovy rice flour, had a yellow color, had a textured crunchy and salty taste. Crackers had a moisture content of 4,89%, acid insoluble ash content of 0,11% and protein content of 13,28%, an average calcium content value of 4339,19 mg/100g and an average value of beta-carotene content of 1,015 mg/kg